Socio-economy of Solidarity: A Theory to Shed Light on Alternative Social and Economic Experiences (2014)
In recent years, the concepts of solidarity economy, or socio-economy of solidarity, as we have preferred to call it in this work, has become widespread in the world of alternative ideas and economic practices. This field refers to numerous economic experiences (in the diverse phases of production, distribution, consumption and accumulation) involving solidarity, based on such values as cooperation, democratic participation, fairness, and care of the environment. The proposal of this work is to understand how economy and solidarity can be worked together. We will discover the existence of solidarity economic behaviors and even of solidarity enterprises which together form part of an economic sector that is different from both: the capitalist sector and the state sector. The idea of a socio economy of solidarity refers to the importance of understanding the interwoven economy (Polanyi) in a particular framework of social rules. Therefore, our approach distances itself and questions the misnamed homooeconomicus, proposing a more complex and realistic look at our socio-economic motivations, and a theory more in line with a plural economy in which solidarity behaviors and enterprises (cooperatives, fair trade organizations, responsible consumption organizations, ethical financeorganizations, popular economic organizations, associative networks, etc.) can be analyzed and interpreted from a scientific perspective in which such disciplines as sociology, economics, anthropology and economic history all converge.